2019
DOI: 10.1111/1348-0421.12754
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle‐adjuvanted S protein induces a strong antigen‐specific IgG response against severe acute respiratory syndrome‐related coronavirus infection, but fails to induce protective antibodies and limit eosinophilic infiltration in lungs

Abstract: The spike (S) protein of coronavirus, which binds to cellular receptors and mediates membrane fusion for cell entry, is a candidate vaccine target for blocking coronavirus infection. However, some animal studies have suggested that inadequate immunization against severe acute respiratory syndrome coronavirus (SARS-CoV) induces a lung eosinophilic immunopathology upon infection. The present study evaluated two kinds of vaccine adjuvants for use with recombinant S protein: gold nanoparticles (AuNPs), which are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
170
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(171 citation statements)
references
References 71 publications
(107 reference statements)
1
170
0
Order By: Relevance
“…Spike protein has also been the focus for vaccine development. For example, mice vaccinated with DNA or subunit vaccines composed of spike proteins (or receptor-binding domain of spike proteins) and adjuvants had high titers of immunoglobulin G antibodies and were protected from SARS-CoV-1 or Middle East respiratory syndrome coronavirus infection (Du et al 2010, Du et al 2007, Honda-Okubo et al 2015, Iwata-Yoshikawa et al 2014, Li et al 2013, Lu et al 2010, Sekimukai et al 2020, Yang et al 2004, Zhao et al 2014. Toll-like receptor ligands, delta inulin, and monophosphoryl lipid A were reported as effective adjuvants to be combined with subunit vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Spike protein has also been the focus for vaccine development. For example, mice vaccinated with DNA or subunit vaccines composed of spike proteins (or receptor-binding domain of spike proteins) and adjuvants had high titers of immunoglobulin G antibodies and were protected from SARS-CoV-1 or Middle East respiratory syndrome coronavirus infection (Du et al 2010, Du et al 2007, Honda-Okubo et al 2015, Iwata-Yoshikawa et al 2014, Li et al 2013, Lu et al 2010, Sekimukai et al 2020, Yang et al 2004, Zhao et al 2014. Toll-like receptor ligands, delta inulin, and monophosphoryl lipid A were reported as effective adjuvants to be combined with subunit vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Spike protein has also been the focus for vaccine development (20). High titers of IgG antibodies were reported to protect mice from SARS-CoV or MERS-CoV viral infection in mice vaccinated by DNA or subunit vaccines composed by Spike proteins (or RBD of Spike proteins) and adjuvants (21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…a comparison with a commercial whole inactivated viral vaccine also showed that the GNP conjugate provided better antiviral protection. GNPs conjugated to the S protein of severe acute respiratory syndrome-related coronavirus induced a strong IgG response upon immunization of mice [114].…”
Section: Article Highlightsmentioning
confidence: 99%